2006
DOI: 10.1029/2005jc003171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Yellow Sea Warm Current on the winter temperature distribution in a numerical model

Abstract: [1] The temperature distribution and circulation patterns in the Yellow Sea (YS) are examined by using a wave-tide-circulation coupled numerical model. This model sufficiently reproduces the variation of the warm tongue structure of the Yellow Sea Warm Current (YSWC) from the double branches flowing along the YS Trough and the western 60 m isobath in January to the single stream along the western temperature front in March. This is observed in both the long-term monthly climatology and the satellite-based sea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 18 publications
3
36
1
Order By: Relevance
“…This horizontal distribution of net SHF from the above data sets is different from the work of Ma et al (2006) which showed the largest negative net SHF in the central HS. Their calculation was made by using a simple atmospheric feedback scheme (Harney, 1971), though their results were integrated from October to March.…”
Section: The Hs Shf In Wintercontrasting
confidence: 52%
See 2 more Smart Citations
“…This horizontal distribution of net SHF from the above data sets is different from the work of Ma et al (2006) which showed the largest negative net SHF in the central HS. Their calculation was made by using a simple atmospheric feedback scheme (Harney, 1971), though their results were integrated from October to March.…”
Section: The Hs Shf In Wintercontrasting
confidence: 52%
“…Although there were some minor differences in their minimum value, all data sources from this study exhibited the same trend in the net SHF variation in the shallow water and warm tongue area, with the largest surface cooling occurred in December. However, according to Ma et al (2006), the lowest value in the shallow water described was in October (Fig. 13a in Ma et al, 2006), while in the warm tongue area, the net SHF reached a minimum value in January.…”
Section: The Hs Shf In Wintermentioning
confidence: 93%
See 1 more Smart Citation
“…Lv et al (2009) found that the winter salinity of the northern YS at depths of 0, 10, and 20 m has shown an increase since the 1950s. Similarly, Ma et al (2006) reported that the mean salinity of the Dalian-Chengshantou section was increasing. Jiang et al (2007) analyzed the bottom salinity of a station at the center of the Dalian-Chengshantou section and found no clear salinity changes in the NYSCWM.…”
Section: Introductionmentioning
confidence: 99%
“…The salinity trend of the coastal area is positive and may be related to the coastal current from the northern YS. The salinity of the water (Lin et al 2001;Ma et al 2006;Lv et al 2009). Wu et al (2004) concluded that the sustained and rapid reduction in Yellow River runoff was a major reason for the increased salinity in the Bohai Sea.…”
Section: Interannual Salinity Trendmentioning
confidence: 99%